Nanoarchitectonics of point-of-care diagnostics for sweat biomarkers analysis - Xuan Lin; Arya Vasanth; Aditya Ashok; Hoang-Phuong Phan; Kevin M. Koo; Mohammed A. Amin; Yusuf Valentino Kaneti; Carlos Salomon; Md Shahriar A. Hossain; Yusuke Yamauchi; Mostafa Kamal Masud (Nano Materials Science)
Sweat contains numerous vital biomarkers such as metabolites, electrolytes, proteins, nucleic acids and antigens that reflect hydration status, exhaustion, nutrition, and physiological changes. Conventional healthcare diagnosis relies on disease diagnostics in sophisticated centralized laboratories with invasive sample collection (e.g., chemical analyses, plasma separation via centrifugation, tissue biopsy, etc.). Cutting-edge point-of-care diagnostics for sweat biomarker analysis allow for non-invasive monitoring of physiologically related biomarkers in sweat and real-time health status tracking. Moreover, using advanced nanoarchitectures, including nanostructured platforms and nanoparticles, can enhance the specificity, sensitivity, wearability and widen the sensing modality of sweat biosensors. Herein, we comprehensively review the secretory mechanisms, clinical uses of sweat biomarkers, and the design, principle, and latest technologies of sweat biosensors. With an emphasis on cutting-edge technologies for sweat biomarker analysis, this review chronicles the issues associated with the current sweat biomarkers analysis of sweat biomarkers and provides insights into strategies for enhancing the translation of such biosensors into routine clinical practice.